FC 127SODIUM-GLUCOSE COTRANSPORTER 2 INHIBITORS (SGLT2I) SHORT-TERM OUTCOME IN DIABETIC KIDNEY TRANSPLANT RECIPIENTS. (29th May 2021) - Yagan, Jude; Mahmoud, Tarek S H; Geith, Osama
Abstract: Background and Aims: The emergence of positive data on the use of sodium glucose co-transporter inhibitors (SGLT2i) in the last several years, begged the question of whether their positive outcomes can be seen in kidney transplant recipients, as they have the same and even more pronounced cardiovascular risk factors than the general population and in addition, we got better in improving graft and patients survival in the short term, but we lack the tools to improve long term patients and graft survival where so many patients die from cardiovascular disease with a functioning graft or lose their graft from chronic changes and chronic antibody mediated rejection with difficult to control blood pressure and proteinuria For these reasons we need more powerful tools, like the SGLT2i bearing in mind the unique side effects that might be amplified in kidney transplant recipients receiving immunosuppression like urinary tract infection, and the dip in serum creatinine. Method: We collected data retrospectively from transplant records of patients with type II diabetes mellitus (T2D) or post-transplant diabetes mellitus (PTDM) (n=79) who were receiving SGLT2i agents plus standard of care [SOC] management and compared them to (n=56) similar diabetic patients who were only on SOC management. Results: The two groups were comparable regarding age, sex, type of donor, type of diabetes (T2D PTDM), post-transplant period, induction immunosuppression and use of CNI. Though improvement of HbA1c was not significantly different between the two groups, patients on SGLT2i showed better drop in HbA1c compared to the SOC group (0.7% versus 0.5% respectively). Reduction of BMI was equal between the two groups (-1.1%) and there was no significant difference in the number of blood pressure medications (average 2 drugs per patient). Kidney function was assessed by the eGFR using CKD-EPI equation and by urine albumin/creatinine ratio (ACR). The eGFR was calculated at start then at 1, 3, 6 and 12 months. In SGLT2i group, eGFR showed a dip at 3 months (from 66 to 63.35 ml/min) then started to improve gradually toward the end of the year and maintained at a level close to baseline (65.44 ml/min). The SOC group showed gradual drop in eGFR over the year from 65.76 to 63.19 ml/min. Urine ACR reduced in the SGLT2i group from 48.79 to 23.79 mg/mmol creatinine and increased from 42.84 to 63.16 mg/mmol creatinine in the SOC group. The incidences of graft rejection, urinary tract infection, genital infection, myocardial infarction, heart failure or cerebrovascular stroke were not different between the groups. Conclusion: Use of SGLT2i in managing diabetic patients post kidney transplantation is safe and has better short-term outcomes on renal function with comparable safety compared to standard of care therapy.